The Management of Integrated Madrasah-Islamic Boarding School Curriculum to Enhance Graduated Student Quality At Azmania Boarding School Ponorogo - Septian Eka Pratiwi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2024)
This study analyzed the curriculum according to the institution's basic values. To improve the quality of graduated students, the research aims to understand how to develop, organize, administer, and oversee the combined madrasah-Islamic Boarding School curriculum. This study employs a case study methodology and a qualitative approach. Participatory observation, interviews, and documentation are used to get the data. Techniques for data reduction, data presentation, conclusion, and verification are used to analyze data. The study's findings indicate that purpose, target student, and graduated student quality are all included in integrated curriculum planning. School organization, curriculum material, and the distribution of teacher responsibilities during the teaching and learning process make up curriculum implementation. Determining the roles and responsibilities of instructors in teaching and learning activities is part of the implementation. Periodically, beginning with daily, weekly, monthly, semester-end, and year-end, supervisions are conducted.